Population pharmacokinetics of ponesimod and its primary metabolites in healthy and organ-impaired subjects - Lott, Dominik; Krause, Andreas; Dingemanse, Jasper; Lehr, Thorsten (European journal of pharmaceutical sciences, 2016)
Ponesimod, a selective, orally active S1P1 receptor modulator, reduces total blood lymphocyte counts by blocking the egress of lymphocytes from lymphoid organs. It is currently in clinical development for the treatment of relapsing-remitting multiple sclerosis. Ponesimod has two primary metabolites, M12 and M13, that circulate in human plasma. The work presented in this paper predicts and quantifies the accumulation of ponesimod and both metabolites in healthy and organ-impaired subjects. Based on clinical data including studies in renally and hepatically impaired subjects, a population pharmacokinetic (PK) model was developed to characterize the PK of ponesimod and its primary metabolites and to qualify and quantify the influence of organ impairment on the concentration-time profiles of these compounds. As hepatic and renal function are critical for the elimination of the majority of drugs, being able to quantify their influence is important for the treatment in these populations. The PK of ponesimod and its metabolites were characterized by 2 compartments for each of the analytes, inter-connected via a liver compartment that serves as a physiologically meaningful approach to model first-pass metabolism. Absorption and elimination were described by first-order processes whereas metabolism was found to be saturable at supratherapeutic doses. Body weight and hepatic impairment were identified as significant covariates. Whereas the effect of body weight is small and within the margins of between-subject variability, hepatic impairment markedly affects the PK of ponesimod and its metabolites with up to 9-fold higher steady-state exposure in subjects with severe hepatic impairment. [Display omitted]